Eco-Friendly and Community Sustainable Textile Fabric Dyeing Methods From Thai Buffalo Manure: From Pasture to Fashion Designer - Suthasini Bureekhampun; Chanida Maneepun (SAGE Open, 2021)
The research objective was to study local traditional wisdom of the art of producing fabric dye from fresh buffalo manure (FBM). Data were collected from rural weaving community cooperative (co-op) members and experts in Thailand’s northeastern Mekong River province of Nakhon Phanom. The study’s Method 1 added buffalo dung water, salt, and a mordant together, which was brought to a boil for 30 minutes. Method 2 added buffalo dung water and salt, which was brought to a boil for 10 minutes, after which a mordant agent was added, then boiled for an additional 30 minutes. There were five different formulas for each method using a different mordant. Results revealed that Method 1 had the best dyeing solution and produced a consistent, commercially usable, washable fabric with three-tone coloring and long-lasting yarn. Method 1 also used a hot dyeing technique in which cotton yarn and FBM were disinfected in a boiling vat while natural odor-reducing additives were added. Moreover, Method 1 consisted of either (1) FBM, salt, and lye, (2) FBM, salt, and muddy water, or (3) only salt added to FBM. These three solutions yielded a material in which testing by the Thailand Textile Institute (THTI) using ISO standards was determined to have a moderate degree of lightfastness, as well as an excellent resistance to color fading after washing. The study is important as it adds a wealth of knowledge to the literature concerning eco-friendly eco-fashion, sustainable products, and economically viable traditional handicraft textile production techniques.
Keywords: Dyeing and Modifying Textile Fibers; Crafts, Textile, and Design; Fashion and Cultural Textiles